Comparative anatomical study of the taxa from series Verni Mathew (Crocus L.) in Serbia - Raca, I.; Ljubisavljević, I.; Jušković, M.; Ranđelović, N.; Ranđelović, V. (Biologica Nyssana, 2017)
The comparative leaf anatomy of three Crocus L. taxa from series Verni Mathew (Crocus heuffelianus Herb., Crocus tommasinianus Herbert and Crocus kosaninii Pulević) in Serbia is introduced. The general outlook of the cross sections of the leaves was defined with microphotographs. More precisely, leaf shape, leaf surface, mesophyll parenchyma and vascular bundle features were examined. The biggest differences were found at the level of vascular bundles (xylem area, phloem area, sclerenchyma area) and leaf blade features (section height, section length, arm length, white stripe width, lacuna area). In general, listed parameters had the lowest values in C. tommasinianus population, while the highest values could be found in population of C. heuffelianus. Further investigations should be focused on discovering more localities followed by surveying the ecological factors of the habitats.